2021
DOI: 10.1139/cjfas-2020-0388
|View full text |Cite
|
Sign up to set email alerts
|

It’s elemental, my dear Watson: validating seasonal patterns in otolith chemical chronologies

Abstract: Accurate age data is essential for reliable fish stock assessment. Yet many stocks suffer from inconsistencies in age interpretation. A new approach to obtain age makes use of the chemical composition of otoliths. This study validates the periodicity of recurrent patterns in 25Mg, 31P, 34K, 55Mn, 63Cu, 64Zn, 66Zn, 85Rb, 88Sr, 138Ba, and 208Pb in Baltic cod (Gadus morhua) otoliths from tag-recapture and known-age samples. Otolith P concentrations showed the highest consistency in seasonality over the years, wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
25
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 17 publications
(46 citation statements)
references
References 71 publications
(70 reference statements)
2
25
0
Order By: Relevance
“…Also food (Walther et al 2010) and other physiological factors (Sturrock et al 2015) have been suggested to regulate otolith Sr concentrations. However, similar to other studies on Atlantic cod from the North Sea to the Baltic Sea (Hüssy et al 2016;Hüssy et al 2021), the samples used in the present study showed no apparent seasonality in otolith Sr patterns, suggesting that changes in otolith Sr are associated with a change in habitat occupation rather than seasonally varying temperature or growth.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Also food (Walther et al 2010) and other physiological factors (Sturrock et al 2015) have been suggested to regulate otolith Sr concentrations. However, similar to other studies on Atlantic cod from the North Sea to the Baltic Sea (Hüssy et al 2016;Hüssy et al 2021), the samples used in the present study showed no apparent seasonality in otolith Sr patterns, suggesting that changes in otolith Sr are associated with a change in habitat occupation rather than seasonally varying temperature or growth.…”
Section: Discussionsupporting
confidence: 89%
“…Significant differences in particularly Mg, P, Cu and Zn were also detected between a few year classes within the two populations. These elements are under strong physiological control (Campana 1999;Sturrock et al 2015;Limburg et al 2018;Hüssy et al 2020) and have been shown to reflect fish growth (Heimbrand et al 2020;Hüssy et al 2021). Otolith element concentrations of these elements were consistently higher in the North Sea populations.…”
Section: Discussionmentioning
confidence: 99%
“…High-resolution micromilling followed by IRMS has sufficient resolution to detect temperature related cycles in δ 18 O values in cod up to 6 years of age (Høie et al 2004b;Kastelle et al 2017), but long-lived species require higher resolution probe-based secondary ion mass spectrometry (SIMS) (Matta et al 2010). With LA-ICPMS, continuous line scans can capture oscillations in trace elements at high spatial and temporal resolution allowing for the reconstruction of entire life history profiles (Heimbrand et al 2020;Hüssy et al 2016bHüssy et al , 2021a. Alternatively, high-resolution 2D elemental maps, produced using LA-ICPMS (Artetxe-Arrate et al 2021;Heimbrand et al 2020;McGowan et al 2014), particle induced x-ray emission (PIXE) (Halden et al 2000;Walther & Limburg 2012) or scanning X-ray fluorescence microscopy (Hermann et al 2016;Tzeng et al 1999) can reveal spatial heterogeneity in elemental composition, which is useful for observing banding patterns and identifying the optimal transect for analysis of seasonal trends (Heimbrand et al 2020).…”
Section: Methodological Challengesmentioning
confidence: 99%
“…Recently, variations in chemical concentrations have been explored as tracers of physiological processes to underpin age estimation. Elements P, Mg and Zn are associated with the organic matrix of the otolith (Izzo et al 2016b;Miller et al 2006;Thomas et al 2017) and reflect seasonal variations in growth (Heimbrand et al 2020;Hüssy et al 2021a;) (Fig. 1).…”
Section: Seasonal Patterns In Element Concentrationmentioning
confidence: 99%
See 1 more Smart Citation